The Mammalian Circadian Clock Gene Per2 Modulates Cell Death in Response to Oxidative Stress - Magnone, Maria Chiara; Langmesser, Sonja; Bezdek, April Candice; Tallone, Tiziano; Rusconi, Sandro; Albrecht, Urs (Frontiers in Neurology, 2015)
Living in the earth’s oxygenated environment forced organisms to develop strategies to cope with the damaging effects of molecular oxygen known as reactive oxygen species (ROS). Here we show that Per2, a molecular component of the mammalian circadian clock, is involved in regulating a cell’s response to oxidative stress. Mouse embryonic fibroblasts (MEFs) containing a mutation in the Per2 gene are more resistant to cytotoxic effects mediated by ROS than wild type cells which is paralleled by an altered regulation of bcl-2 expression in Per2 mutant MEFs. The elevated survival rate and alteration of NADH/NAD+ ratio in the mutant cells is reversed by introduction of the wild type Per2 gene. Interestingly, clock synchronized cells display a time dependent sensitivity to paraquat, a ROS inducing agent. Our observations indicate that the circadian clock is involved in regulating the fate of a cell to survive or to die in response to oxidative stress, which could have implications for cancer development and the aging process.